Tertiary lymphoid structure drives allograft rejection via IFN-γ-JAK-STAT-dependent atypical memory B cell differentiation - Ma, Lijie; Gong, Shiming; Fang, Jianchen; Feng, Mingxuan; Zhan, Zhenzhen; Xia, Qiang (Frontiers in Immunology, 2025)
BackgroundTertiary lymphoid structure (TLS) is a neogenized, ectopic lymphoid aggregate found in infected, autoimmune and tumour tissues with an activated adaptive immune response. However, a comprehensive understanding of the pathological role, function, and formation of TLS in allograft rejection remains incomplete.MethodsWe enrolled two large retrospective cohorts of liver biopsy (LB) after pediatric living donor liver transplantation (LDLT) and developed a deep learning pathomics (DLP) model. Gene expression profiles and corresponding clinical information of 590 cases were enrolled from three transcriptomic databases, including cohort-GSE193135 (n=337), cohort-GSE145780 (n=235), cohort-Renji (n=18). ESTIMATE, CIBERSORT, XCELL and MCP analyses were performed to visualize the immune landscape. Single-cell RNA-sequencing (scRNA-seq) analysis of 11 LBs after LDLT and multiplexed immunohistochemistry (mIHC) were performed to validate the discoveries of bioinformatics analysis.ResultsWe provided evidence that increased TLS in the liver was closely correlated with allograft rejection, fibrosis, and declined liver function. ScRNA-seq and in vitro co-culture analysis revealed that TLS form through the differentiation of atypical memory B (AtM B) cells via the JAK-STAT signalling pathway, stimulated by IFN-γ from exhausted CD8+ T effector memory (TEM) cells. The presence of TLS resulted in IgG accumulation, initiating pathological antibody-dependent cell-mediated phagocytosis (ADCP) of apoptotic hepatocytes by CD68+ macrophages. Preclinically, blocking JAK1/3 or knocking out Lta in mice limited TLS formation and attenuated allograft rejection in mouse orthotopic liver transplantation models, informing novel therapeutics for allograft rejection pathology.ConclusionWe proposed an efficient DLP model for predicting allograft rejection, and revealed an unexpected immunological mechanism of TLS in allograft rejection livers and clarified an IFN-γ-JAK-STAT-dependent circuit that could be targeted with drugs and transformed AtM B cells into potent instigators of hepatocellular injury in allograft rejection.